PENGARUH NILAI PELANGGAN DAN CITRA MEREK TERHADAP LOYALITAS MEREK MELALUI KEPERCAYAAN MEREK INDIHOME (STUDI KASUS PELANGGAN INDIHOME DI TELKOM AKSES MADIUN) - Novia Nurma Yuliana; Ramadhani Hamzah (Jurnal Ekonomi Bisnis Indonesia, 2022)
The purpose of this study to determine the influence of customer value and brand image on brand trust through IndiHome brand loyalty case study Telkom Access Madiun customers. This research method uses qualitative methods which are analyzed through the Structural Equation Modeling test which is processed with the SmartPLS version 3 program and data collection techniques using a questionnaire and literature studies. The data in this study were taken from questionnaires distributed to Telkom Access Madiun consumers with a total sample of 75 respondents. The results of the direct influence research show that customer value has an effect on brand loyalty, brand trust has an effect on brand loyalty, customer value has had an effect on brand trust, brand image has had an effect on brand trust because of the P Value (< 0.05), while brand image has no effect on brand loyalty because of the P Value (> 0.05). The results of this study show that customer value indirectly influences brand loyalty through brand trust, brand image influences brand loyalty through brand trust because of the P value (< 0.05).